Molecular and functional characterization of ovis aries IFN-epsilon. (March 2020) - Guo, Yongli; Song, Zhifeng; Cheng, Xintong; Wang, Yujiao; Luo, Xiuxin; An, Ran; Wang, Junwei; Gao, Mingchun
Highlights: OvIFN-ε has the typical molecular characterization of IFN-εs. OvIFN-ε is highly transcribed in the liver, lung, brain, skin, ovary and uterus. OvIFN-ε has a cross-protective effect among different species. OvIFN-ε can inhibit the VSV and BVDV replication. OvIFN-ε enhances the transcription of ISG15, Mx1 and OAS gene. Abstract: Interferon-epsilon (IFN-ε) is a type I IFN playing an essential role in innate and adaptive immunity against viral infection. O vis aries IFN-ε (OvIFN-ε), consisting of 582 bp and which encodes a protein of 193 amino acids containing a signal peptide of 21 amino acids, was cloned and characterized. OvIFN-ε shares 51.6∼ 86.5% similarity to other species of IFN-ε, and evolves from the IFN-ε branch but not the other types of IFN. Additionally, OvIFN-ε gene is well conserved during evolution, and is highly transcribed in the liver, lung, brain, skin, ovary and uterus. Recombinant protein of OvIFN-ε was expressed in Escherichia coli and purified with nickel chelated column, which exhibited broad antiviral activity in vitro, sensitivity of trypsin, and stability of pH and temperature to some extent. Furthermore, OvIFN-ε could induce the transcription of ISG15, Mx1 and OAS in a time-dependent manner, as well as inhibit the VSV and BVDV replication in Ovis aries peripheral blood lymphocyte cells and MDBK cells. This study revealed OvIFN-ε has the typical characterization of type I IFNs and exerts antiviral activity against VSV and BVDV, and induces the expression of ISGs, which not only enriches the understanding of IFN-ε, but also facilitates further research on the antiviral defense responses of Ovis aries .